2021
DOI: 10.2196/30845
|View full text |Cite
|
Sign up to set email alerts
|

Delivering an Online Cognitive Behavioral Therapy Program to Address Mental Health Challenges Faced by Correctional Workers and Other Public Safety Personnel: Protocol for a Mixed Methods Study

Abstract: Background Public safety personnel have regular and often intense exposure to potentially traumatic events at work, especially workplace violence in the case of correctional workers. Subsequently, correctional workers are at higher risk of developing mental health problems such as posttraumatic stress disorder. Public safety personnel are up to 4 times more likely to experience suicidal ideation, suicidal attempts, and death by suicide compared to the general population. Despite this high prevalenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The gap in effective and timely support can potentially exacerbate the effects of potentially psychologically traumatic and violent incidents on correctional workers. It may even contribute to the development of mental disorders such as posttraumatic stress disorder—a disorder and its comorbidities that is prevalent among correctional workers (Alavi et al, 2021; Finney et al, 2013; Genest et al, 2021; Norman & Ricciardelli, 2021; Regehr et al, 2019; Ricciardelli & Carleton, 2021; Ricciardelli et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The gap in effective and timely support can potentially exacerbate the effects of potentially psychologically traumatic and violent incidents on correctional workers. It may even contribute to the development of mental disorders such as posttraumatic stress disorder—a disorder and its comorbidities that is prevalent among correctional workers (Alavi et al, 2021; Finney et al, 2013; Genest et al, 2021; Norman & Ricciardelli, 2021; Regehr et al, 2019; Ricciardelli & Carleton, 2021; Ricciardelli et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding mental health interventions, respondents' accounts of available treatment options point to the need for a special correctional mental health paradigm that reflects the characteristics and sources of stress among correctional workers. There is some recent recognition of this need in the extant literature as Alavi et al (2021) have identified some of the benefits of delivering an online cognitive behavioral therapy program to address the mental health challenges experienced by correctional workers and other public safety personnel. Our data, in tandem, speak to the need for a model that is responsive to correctional-specific work stressors, available easily and immediately (i.e., in the aftermath of an event), and comprehensive and continuous so as to adequately and sufficiently respond to the complexity of occupational stress injuries.…”
Section: Improvements In the Physical Environmentmentioning
confidence: 99%
“…The lived experiences of CWs can provide rich and detailed insights into the dynamics of the mental health and treatment-seeking challenges they face in their work environment. The current study is the first phase of a larger randomized controlled trial (RCT) that will investigate the efficacy of online psychotherapy in this population ( 11 ). The virtual platform (Online Psychotherapy Tool; OPTT) offers electronic cognitive behavioral therapy (e-CBT), the first-line psychotherapeutic treatment for many mental health disorders ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In-depth 1:1 interviews and focus groups focused on how CWs interacted with prisoners and colleagues, their work conditions and conflicts, mental health challenges they faced, perceptions of mental health resources and support, and their attitudes toward mental health care. Participants were also asked to provide feedback on previous modules for PTSD and depression available on OPTT ( 11 , 15 ). The findings of the current study will guide the development and evaluation of e-CBT programs for CWs in the subsequent phases.…”
Section: Introductionmentioning
confidence: 99%
“…PSPNET's ICBT has demonstrated promising initial outcomes for treating symptoms of several mental disorders among PSP [30]. At the time this article was written, at least two other Canadian research groups were also developing ICBT interventions for PSP [31,32].…”
Section: Introductionmentioning
confidence: 99%